A novel method for quantitatively evaluating agricultural vulnerability to climate change. (January 2015) - Dong, Zhiqiang; Pan, Zhihua; An, Pingli; Wang, Liwei; Zhang, Jingting; He, Di; Han, Huijie; Pan, Xuebiao
Highlights: A novel method is advanced for quantitative evaluation of agricultural vulnerability to climate change. This method owns clear expressions of vulnerability components and can reflect the objective reality. The method can conveniently compare the different crops' vulnerability in the same region, and compare a crop's vulnerability in different regions. This method highlights the impacts of climate change based on the basic period and the study period. The method can assess vulnerable degree based on different vulnerability levels. Abstract: Climate change has affected all aspects of human societal development as a global problem, especially agriculture, which is closely related to human survival. Evaluating vulnerability can be helpful in assessing the impact of climate change and analyzing the effectiveness and adaptive degrees of different countermeasures to provide a reliable basis for addressing climate change. However, determining how to quantitatively evaluate vulnerability is a difficult problem and a pressing question. We propose an objective and quantitative assessment method for agricultural vulnerability under climate change according to the Intergovernmental Panel on Climate Change's definition of vulnerability and a framework of sensitivity, adaptive capacity, and exposure degree. We explain the practical and objective attributes of this method using Wuchuan County in Inner Mongolia as an example. This assessment method can clarify the effects of climate change on agriculture and effective countermeasures, as well as contribute to the sustainable agricultural development.